Ultra-smooth and space-filling mineral films generated via particle accretion processes. Issue 6 (24th June 2019) - Harris, Joe; Mey, Ingo P.; Böhm, Corinna F.; Trinh, Thi Thanh Huyen; Leupold, Simon; Prinz, Carsten; Tripal, Philipp; Palmisano, Ralf; Wolf, Stephan E.
Abstract : Well-tuned bioinspired mineralization via liquid mineral precursors yields ultra-smooth, space-filling bodies, transgressing the supremum of packing densities of nonclassical crystallization. Abstract : Nonclassical crystallization typically yields materials with pronounced roughness and porosity as it is driven by nanoparticle self-organization. Here, we demonstrate that bio-inspired nonclassical mineralization via magnesium-doped polymer-induced liquid precursors (PILP) can yield ultra-smooth and space-filling CaCO3 films featuring an unprecedented low roughness of 0.285 nm.